Activation of the l-arginine nitric oxide pathway in severe sepsis. Issue 3 (1st March 1997) - Duke, Trevor; South, Mike; Stewart, Alastair
Abstract : AIMS: To determine in children with sepsis syndrome and septic shock the time course of nitric oxide metabolites: nitrate and nitrite (nitrogen oxides). To determine whether serum concentrations of nitrogen oxides distinguished those children who died from sepsis from those who survived; those who required prolonged inotropic support compared with those who did not; and whether there was any relationship of the levels of nitrogen oxides to markers of tissue perfusion. METHODS: Nitrogen oxides were measured in 30 children with sepsis syndrome or septic shock at admission, 12, 24, and 48 hours. A non-septic control group had serum nitrogen oxides measured at admission. Markers of haemodynamics and tissue perfusion measured were mean arterial pressure, blood lactate, base deficit, gastric intramucosal pH, and deltaCO2 (DCO2 : the difference between arterial and gastric intraluminal carbon dioxide tensions). Inotrope doses, number of organ systems failing at 48 hours, and outcome as survival were recorded. RESULTS: Children with sepsis had increased nitrogen oxide concentrations at presentation compared with a group of non-septic controls. Children with organ failure at 48 hours had higher serum nitrogen oxide concentrations than those with sepsis uncomplicated by organ failure at 48 hours. There was no difference in nitrogen oxide when patients were subgrouped according to the receipt of inotropes at 48 hours, and no association with markers of tissue perfusion, or survival. CONCLUSIONS: While this study shows that nitric oxide production is increased in sepsis in children, there was a limited relationship with clinically important markers of illness severity and no relationship to survival.